The Jews of Białystok during World War II and the Holocaust - Bender, Sara (The Tauber Institute for the Study of European Jewry Series, 2008)
The interwar period -- Biaystok under Soviet rule -- The early days of the German occupation -- The period of calm, November 1941-November 1942 -- The early days of the underground -- The first aktion, February 1943 -- The interim period, March-May 1943 -- The end of the ghetto -- A comparative study of the Biaystok ghetto and other ghettos